PERJALANAN MENUJU PEKAN OLAHRAGA NASIONAL 2024 (STUDI PORTOFOLIO ATLET SELANCAR ANGIN) - Sefiani, Nabila; Sujarwo, Sujarwo; Sari, Eka Fitri Novita (UNIVERSITAS NEGERI MAKASSSAR, 2025)
This study aims to explore the journey of a Windsurfing athlete in preparing for the XXI National Sports Week (PON) Aceh-North Sumatra 2024. Using an autoethnographic approach, the study reveals the technical, mental, and infrastructural challenges faced by the athlete, as well as the roles of nutrition, sleep, and social support in maintaining athletic performance. The findings indicate that adapting to the new iQFoil equipment was a major challenge, requiring mastery of new techniques. Balanced nutrition and quality sleep proved crucial in maintaining stamina and recovery. Moreover, support from coaches, family, and sponsors significantly influenced the athlete's motivation and mental resilience. However, limited training facilities and high-quality domestic competitions remain substantial barriers to Windsurfing development in Indonesia. This study recommends improving facilities, organizing domestic competitions, and offering internationally certified coaching programs to enhance athlete development. With long-term investments in infrastructure and training programs, Indonesia has the potential to produce world-class Windsurfing athletes